Kinerja Mesin Pemisah Potongan Tangkai dan Daun Teh - Agus Sutejo; Sutrisno Suro Mardjan; Wawan Hermawan; Desrial Desrial (The University of Lampung, 2018)
The quality of dried tea depends on the condition of raw materials and processing methods. The problem in the tea processing is the mixture of pieces of stalks and leaves. This research aims to examine the performance of stalks and leaves machine separator based on the difference of suction velocity and the terminal velocity of the material. The separator was designed according to the physical and aerodynamic properties of tea leaves. The performance of the separator was done by calculating the separating efficiency of five combined treatments (P, P1a, P1b, P0a, and P0b) and calculating the separating capacity with three feeding treatments (0.4 kg/sec, 0.5 kg/sec, and 0.6 kg/sec). Physical property observation of the tea leaves obtained an average mass 0.143 kg/m² which means the theoretical suction pressure needed is about 1.4 Pa. The actual terminal velocity measured as 7.5 m/sec for the stalk pieces and 3.0 m/sec for the leaf pieces. The optimum separating efficiency was obtained at P treatment, it was about 97.6 %, with average suction ir velocity 3.15 m/s. Optimum separating capacity was obtained about 354.29 kg/hour.